2011
DOI: 10.1523/jneurosci.0388-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Kainate Receptors in Interplay with INaP Shift the Sparse Firing of Dentate Granule Cells to a Sustained Rhythmic Mode in Temporal Lobe Epilepsy

Abstract: Dentate granule cells, at the gate of the hippocampus, use coincidence detection of synaptic inputs to code afferent information under a sparse firing regime. In both human patients and animal models of temporal lobe epilepsy, mossy fibers sprout to form an aberrant glutamatergic network between dentate granule cells. These new synapses operate via long-lasting kainate receptor-mediated events, which are not present in the naive condition. Here, we report that in chronic epileptic rat, aberrant kainate recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 44 publications
(76 reference statements)
5
60
0
Order By: Relevance
“…For example, the upregulation of the Grik3 gene (Fig. 7) may contribute to the hypersusceptible phenotype, as long-lasting kainate receptor-mediated events have been associated with sustained, rhythmic firing in a rodent model of temporal lobe epilepsy (Artinian et al 2011). The GABA A -ε subunit, encoded by the Gabre gene, is associated with increased spontaneous channel activity (Bollan et al 2008), and therefore, the prolonged downregulation of the Gabre gene following PIC challenge (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the upregulation of the Grik3 gene (Fig. 7) may contribute to the hypersusceptible phenotype, as long-lasting kainate receptor-mediated events have been associated with sustained, rhythmic firing in a rodent model of temporal lobe epilepsy (Artinian et al 2011). The GABA A -ε subunit, encoded by the Gabre gene, is associated with increased spontaneous channel activity (Bollan et al 2008), and therefore, the prolonged downregulation of the Gabre gene following PIC challenge (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the plasticity of PP-DGC firing pattern induced by rMF-CT is a Ca 2+ -dependent process. Previous studies have reported I NaP as a likely candidate in the modulation of firing rate 44,56 . We then challenged the role of I NaP in the long-lasting change of PP-DGC firing pattern.…”
Section: Long-lasting Disruption Of Pp-evoked Dgc Sparse Firing Inducmentioning
confidence: 94%
“…Moreover, recordings in voltageclamp mode revealed no significant difference of the excitatory postsynaptic current (EPSC) strength between control (1 st EPSC amplitude: -70 ± 6 pA, n = 11) and epileptic conditions (-81 ± 9 pA, n = 7, p = 0.119) (Fig 2A, B). We have previously reported that rMF synapses, operating via KARs, drive an aberrant sustained firing regime in DGCs when recruited in the gamma frequency range 44 . To evaluate the long-lasting consequence of this synaptopathic activity on .…”
Section: Long-lasting Disruption Of Pp-evoked Dgc Sparse Firing Inducmentioning
confidence: 99%
“…The convulsant activity of kainate has not previously been shown to occur independently of GluK1 KARs. However, this conclusion is not surprising given the more restricted expression and lower density of GluK1 KARs in brain regions relevant to seizures than GluK2 KARs (Bahn et al, 1994;.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which this observation can be generalized to other epileptogenesis models remains to be determined. There is evidence for enhanced functional activity of KARs at aberrant mossy fiber-granule cell synapses in a poststatus epilepticus model of temporal lobe epilepsy (Epsztein et al, 2005;Artinian et al, 2011), suggesting that there could be differences among epileptogenesis models.…”
mentioning
confidence: 99%